What must be the Pillars of Iran's Health System in 2025? Values and Principles of Health System Reform Plan - Fateme Rajabi; Hamid Esmailzadeh; Narges Rostamigooran; Reza MajdZadeh (Tehran University of Medical Sciences, 2013)
Background: Preparing long term reformatory plan for the health system, like other macro plans, requires guiding principles which is according to the values, and as a bridge, connect the ideals and values to the goals. This study was designed with the purpose of explaining the values and principles of health system, and as a pre-requisite to compilation of Iran's health system reform plan at 2025.Method: The document of values and principles of health system reform plan for 2025 was developed by reviewing the literature and receiving the opinions of senior experts of health system, and was criticized in focus group discussion sessions of experts and decision makers.Results: The values of Iran are: dignity of human, the right to maximum attainable level of health, comprehensive health, equity and social cohesion. The principles of this health system include: institutionalizing the ethical values, responsiveness and accountability, equitable access (utilization), prevention and health promotion, community participation, inter-sectoral collaboration, integrated stewardship, benefit from innovation and desired technology, human resources promotion and excellence and harmony.Conclusion: Based on the perception of cultural and religious teachings in Iran, protecting of human dignity and human prosperity are the ultimate social goal. In this sense, health and healthy humans, in its holistic concept (physical, mental, social health and spiritual) are the center and development in any form should lead to the human prosperity in a way that each of the individuals could enjoy the maximum attainable level of health in its holistic meaning and in a faire manner.